A rare case of neuro regression in an Indian child: beyond the realm of nervous system - Srivastava, Preeti; Sunder, Sarala; Sarkar, Nilanjan (International Journal of Contemporary Pediatrics, 2020)
When we encounter a child with dysmorphism and developmental delay or regression, we are prompted to think on lines of a disorder of nervous system. However, at times a disorder primarily involving another system, more importantly, a modifiable condition, could be responsible for same phenotypic presentation. A 6 years old male child with global developmental delay, dysmorphism, seizures and new onset regression appeared to be suffering from some neurodegenerative disorder on first impression. As detailed examination, lab investigations and imaging findings were noted, a rare endocrinal disorder was unravelled and a diagnosis of pseudohypoparathyroidism (PHP) type 1A was made and was genetically confirmed.